ANALISIS RISIKO DAN MITIGASI PADA PENGIRIMAN ALAT BERAT DENGAN METODE ERM - Sihombing, Tulus Martua; Adiprasetyo, Wahyudi; Irajani, Yehezkhiel Shallom (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Heavy lift delivery activities are complex and complicated, the handling process is also different when compared to loads in general due to excess dimension factors, both length, width, and height. There are constraints and risks in the delivery of heavy equipment. This study aims to analyze operational risks arising from heavy equipment delivery activities at PT Daily Express Cargo. By analyzing the risks that may occur, it is expected that the company can take the right decisions and actions to overcome the risks. The research method used is the Enterprise Risk Management (ERM) method with descriptive analysis and qualitative approach. Data collection techniques through in-person interviews and questionnaires. In this study, twenty operational risks were found. After identification and risk assessment, there are four risk levels, namely high, medium, low, and very low levels. At a high level there are 2 risks, at a medium level there are 5 risks, at a low level there are 5 risks, and at a very low level there are 8 risks. Each risk that arises requires appropriate risk control tailored to its type